BOPO ANALYSIS, NON-PERFORMING LOAN (NPL), AND LOAN TO DEPOSIT RATIO (LDR) TO PROFITABILITY: A Case Study at PT Bank Maluku, Ambon - Pattiruhu, Jozef (jfpublisher, 2022)
Bank is the financial institution with the main business in collecting public money and funds it back in form of credit. Also, provide services in payment traffic and money circulation. Therefore, in doing its daily business activities, banks need to have money in order to provide the credit. In providing credit to customers, Bank management implements various policies in lending process. This study aims to determine and analyze whether BOPO, Non Performing Loan (NPL), and Loan to Deposit Ratio (LDR) have a significant effect on the profitability of PT. Maluku–Malut Bank in Ambon City or not with the research data from 2015–2019 periods. The analytical method used is multiple linear regressions using t-test to examine the hypothesis. Based on the research, the results show that: BOPO has a positive effect on profitability; NPL has a negative effect on profitability; furthermore, LDR has a negative effect on the profitability of PT. Maluku–Malut Bank in Ambon City.